Diagnostic tools for measuring the effectiveness of fairy tale-based language teaching in preschool education - Israilova, Dildora Atxamovna (The Lingua Spectrum, 2026)
This study examines diagnostic tools to assess the effectiveness of fairy-tale–based language teaching in preschool settings. A mixed‑methods quasi‑experimental design involved 120 children (ages 5–6) assigned to an intervention group that received a 10‑week fairy-tale curriculum and a control group that followed standard language activities. Diagnostic instruments included standardized receptive and expressive vocabulary tests, narrative retelling tasks scored with a validated rubric (story structure, cohesion, lexical richness), phonological awareness probes, observational checklists for communicative engagement, and teacher/parent questionnaires on functional language use. Pre‑ and post‑intervention measurements were complemented by audio–video recordings for microanalysis and inter‑rater reliability checks. Results showed statistically significant gains in vocabulary breadth, narrative complexity, and phonological awareness in the fairy tale group compared with controls; observational data also indicated higher sustained engagement and turn‑taking. The combined battery demonstrated strong sensitivity to short‑term gains and acceptable reliability (Cronbach’s α > .80; inter‑rater agreement > .85). The paper discusses practical guidelines for implementing the diagnostic suite, emphasizes the need for culturally and linguistically adapted materials, and recommends longitudinal follow‑up to evaluate sustained effects. These tools support evidence‑based evaluation of story‑based pedagogies in early language development.